HUKUM PASAR MODAL DAN TANGGUNG JAWAB SOSIAL - Salami, Rochani Urip (Jurnal Dinamika Hukum, 2011)
Each state has always tried to promote development, prosperity and prosperity of its people. One methode that tends to be done by the state is to attract as many foreign investments into the country. In the Investment Law, there are three principles: First, the rule of law which is manifested in several important principles such asequal treatment between investment of domestic and foreign, transparency and accountability; Second, Guarantees against nationalization affirmation action in the dispute settlement, and Third, Simplification of investment procedures and licensing service through an integrated one stop mechanism.  Economic development is not just the responsibility of the goverment and its citizens, but also the responsibility of investor. Arrangements os social responsibility for infestor is the legal basic for investor in caring the surrounding environment, so with the implementation of social responsibility by companies in a region, indirectly the company/investors assist in improve the welfare of local communities.Key words: capital market law, corporate social responsibility, globalization